Blockchain-assisted industrial automation beyond 5G networks. (July 2022) - Tanwar, Sudeep; Bodkhe, Umesh; Alshehri, Mohammad Dahman; Gupta, Rajesh; Sharma, Ravi
Highlights: A detailed comparison of state-of-the-art surveys for industrial automation. Proposed a decentralized secure industrial automation architecture. Presented a case study on additive manufacturing. Discussed open issues and challenges of industrial automation processes. Abstract: Automation of industrial tasks becomes the necessity of organizations due to high risks and low operational efficiency associated with traditional procedures. The industrial Internet-of-thing (IIoT) has proved it a reality with ubiquitous computing, which interconnects tens of billions of objects, such as devices and machines, for real-time data transfer. However, the rapid increase in the number of connected devices and machines leads to various security issues, such as data modification, sniffing, and many more. Achieving secure and reliable communication between devices becomes challenging as the entire communication takes place over an open channel, i.e., the Internet. Most of the security solutions presented in the literature are centralized and susceptible to security, latency, reliability, and single-point-of-failure issues. Blockchain is a plausible solution to mitigate the aforementioned issues with reduced capital and operating expenditures, whereas the sixth-generation (6G) network makes communication faster and more reliable. Motivated by these facts, this paper presents an exhaustive survey on blockchain-based industrial automation in the 6G environment. Also, a blockchain and 6G-enabled industrial automation architecture for secure and efficient communication among IIoT devices is proposed. This paper also presents a case study on blockchain-based additive manufacturing for designing three-dimensional products to validate the proposed architecture. The performance of the proposed case study is evaluated based on network parameters such as delay, packet loss, scalability, network bandwidth, computation time, and data storage cost. Finally, various research challenges and future directions are suggested in this emerging area.